KONSEP AHLI WARIS DAN AHLI WARIS PENGGANTI: Studi Putusan Hakim Pengadilan Agama - Diana Zuhroh (Al-Ahkam, 2017)
There is a fundamental difference between the rules in Islamic inheritance jurisprudence with the rules of inheritance in the Compilation of Islamic Law. Islamic inheritance jurisprudence rules, on one hand, give inheritance rights to those who are still alive at the time of the testator died. On the other hand, the rules of inheritance in the Compilation of Islamic Law, as defined in Article 171 (c), give inheritance rights to the person who died earlier than the testator, as an attempt to legitimize "substitute heirs" under Article 185 paragraph (1). This difference was not known by the judges in the Religious Courts that have implemented the Compilation of Islamic Law as one source of their substantive laws. This study revealed that in its decision on the case of inheritance proved that the Judges concerned unconsciously, others with skepticism, citing the aforementioned article as one aspect of their legal considerations in determining the beneficiary status of the applicants/plaintiffs, even if the applicant/plaintiff was is "a direct heir" of the testator. Consequently, the resulting verdict is not supported by proper legal considerations.[]Ada perbedaan yang mendasar antara aturan waris dalam Ilmu Faraid dengan aturan waris dalam Kompilasi Hukum Islam. Aturan waris Ilmu Faraid memberikan hak waris kepada orang yang masih hidup di saat pewaris meninggal dunia. Sebaliknya, aturan waris Kompilasi Hukum Islam, sebagaimana ditetapkan dalam Pasal 171 huruf (c), memberikan hak waris kepada orang yang meninggal dunia lebih dahulu daripada si pewaris, sebagai upaya melegitimasi “ahli waris pengganti” yang diatur dalam Pasal 185 ayat (1). Perbedaan ini telah luput dari pengamatan para Hakim di lingkungan Peradilan Agama yang telah lama menerapkan Kompilasi Hukum Islam sebagai salah satu sumber hukum materiilnya. Penelitian ini mengungkapkan bahwa dalam sejumlah putusan waris tampak majelis Hakim yang menangani perkara waris tanpa sadar, sebagian lainnya dengan keraguan, mengutip pasal tersebut sebagai salah satu aspek pertimbangan hukum mereka dalam menetapkan status keahliwarisan para pemohon/ penggugat, sekalipun para pemohon/penggugat itu adalah “ahli waris langsung” dari si pewaris. Akibatnya, diktum putusan yang dilahirkan tidak didukung oleh pertimbangan hukum yang benar.